Climate variability and extractivism exposures: Understanding household perspectives on livelihood resilience in rural Ghana. (December 2022) - Tannor, Salamatu J.; Kelboro, Girma; Greve, Klaus; Borgemeister, Christian; Tischbein, Bernhard
Highlights: Rural livelihoods in Ghanaian mining landscapes are perceived to be exposed simultanous to spontaneous the impact of extractive activities and increasing variability in local climate. Perception of double exposure is differentiated by socio-economic and demographic characteristics of household heads as well as the type of agro- agro-ecological zone and infrastructural disposition of communities. Divorced, widow/widower and unemployed household heads are more likely to perceive double exposure of climate variability and extractivism effect on their livelihoods. Communities affected by mining and forest extractivsm are more likely to perceive double exposure burden. Abstract: The resilience of African rural livelihoods is at risk due to over-reliance on rain-fed agriculture, which increasingly suffers from climate variability. Extractive communities are exposed to changes from extractivism and climate conditions. The double exposure framework is employed to contextualise factors influencing households' perspectives on the overlapping impacts of these change processes on livelihoods. The results affirm a general awareness that both climate variability and extractivism affect rural livelihoods. In addition, contextual factors such as gender, cultural connections, education, type of occupation, agroecological and resource extractivism types significantly influence households' perception of climate variability and extractivism effects on livelihoods. Example, large size households located in the deciduous forest zones are more likely to perceive that their livelihoods are double exposed to climatic variability and extractivism effects. Communities affected by mineral/forestry extractivism are more likely to perceive double exposure of climatic variability and extractivism effects on their livelihood sources. Households expect the national government and extractive companies to provide alternative livelihoods and improve infrastructure to enhance their resilience. The study shows that differential factors underpin the perceived risk of rural livelihoods exposure to climate change and extractivism, thus supporting the need for policy-makers to include mining landscapes in national adaptation programs.